Marketing Mix Affecting Thai Consumers’ Decision Making on Using Services at Bakery Shop in Bangkok - Autsawarattanarak, Kroekwat; Tuvadaratragool, Sumeth (Rajapark Journal, 2024)
This research aimed to study 1) the level of Thai consumers’ decision-making on using services at a bakery shop in Bangkok, 2) the relationship between personal information and Thai consumers’ decision-making on using services at a bakery shop in Bangkok, and 3) the marketing mix affecting Thai consumers’ decision-making on using services at a bakery shop in Bangkok. The quantitative research sample size was 384 Thai consumers using services at a bakery shop in Bangkok. Since the population number is unknown, Cochran’s (1977) sample size formula is applied. The instrument for collecting data was a questionnaire. Statistics used included mean, standard deviation, chi-square, and multiple regression. The research results were as follows: 1) The overall level of Thai consumers’ decision-making when using services at bakery shops in Bangkok is high. Regarding an individual component, the purchasing decision comes first, followed by alternative evaluation, post-purchase behavior, problem recognition, and information search, respectively. 2) The Thai consumers’ personal information, including age, education, and average monthly income, relates to decision-making on using services at a bakery shop in Bangkok at the 0.05 statistical significance level, and 3) The marketing mix, including product, place, promotion, and physical evidence, relates to decision-making on using service at a bakery shop in Bangkok at the 0.05 statistical significance level.